The Many Futures of Digital Journalism - Brian L. Massey (Athens Journal of Mass Media and Communications)
This paper challenges conventional narratives about the future of digital journalism. It argues that digital journalism is not a globally uniform practice with a predictable universal future. Instead, it has many possibility-futures owing to the cultural diversity of the news outlets that engage it and the contexts in which it is engaged. To develop that argument, the paper locates digital journalism as the latest waypoint in humankind’s long quest to send messages ever farther and ever faster. Next, digital journalism is decentered through interdisciplinary theory into a novel framework for forecasting the futures of digital journalism as a diverse global phenomenon.